EFFECTS OF GARCINIA MANGOSTANA LINN PERICARP EXTRACT AND PHYSICAL EXERCISE ON ATHEROEMBOLIC HISTOPATHOLOGIC FEATURES KIDNEY IN WISTAR RATS WITH METABOLIC SYNDROME - Perdana, Evangga Yudha; Miranti, Ika Pawitra (Faculty of Medicine, Diponegoro University, 2024)
Background: Renal atheroembolism is an under-recognized cause of renal failure . Atheroembolism is caused by cholesterol crystals from ulcerated atherosclerotic plaques and is influenced by inflammation and endothelial dysfunction. The formation of complicated atherosclerotic lesions is a prerequisite for the development of cholesterol crystal emboli. Non-pharmacological therapeutic management (such as diet and physical exercise) is an important factor in preventing and reducing the risk of atherogenesis. Garcinia Mangostana Linn pericarp can inhibit the process of atherosclerosis through the reduction of free radicals and improvement of endothelial function Objective: To investigate the effect of Garcinia Mangostana Linn Pericarp administration along with Physical Exercise on the histopathologic features of renal atheroembolism in Wistar rats with metabolic syndrome. Methods: This study is a true experimental study with research subjects in the form of male Rattus norvegicus Wistar rats which were randomly divided into 3 groups. K (not given therapy), P1 (garcinia pericarp extract 800 mg / kg / day with physical exercise), and P2 (nanoemulsion 50 mg / kg / time of administration with physical exercise). Results: In the group treated with garcinia pericarp extract 800 mg/kg bw/day with physical exercise and the group with nanoemulsion 50 mg/kg bw/day with physical exercise, there were no fatty streaks, inflammation, and impaired myocyte coherence. There was 0-5% fibrous connective tissue, one layer of foam cell layer and myocyte-lipid, no cholesterol crystal embolism was found. Conclusion: The administration of Garcinia Mangostana Linn pericarp extract and/or nanoemulsion with physical exercise can have an effect on the histopathological picture of the kidneys of Wistar rats with metabolic syndrome. There was no difference in effect between the two treatments. However, it could not be compared with the group that was not given any treatment because it had died completely before the end of the study period.